The factors affecting financial performance of food and beverage company listed on Bursa Malaysia/ Nurshahira Maskam - Maskam, Nurshahira (2017)
Evaluations of financial performance attract a lot of attention by internal or external users. At this point in time, financial performance becomes important aspect in order to achieve the specific target. Concerning the matter of factors affecting financial performance, the study had been conducted with the purpose to determine the factor affecting the financial performance of the food and beverage company listed on Bursa Malaysia between the years from 2012 to 2016. For analyse a research problem, the dependent and independent variable were chooses from the financial ratio that will focus on the area of liquidity, assets utilization and leverage for the independent variable while probability area for the dependent variable. The study covers 10 company of food and beverage sector listed on Bursa Malaysia as a sample. This study was using panel least square model in order to run multiple regressions analysis for discover the effect of financial indicators on the firm's performance. The result found that current ratio, cash ratio and long-term debt to equity ratio have significant effect the firm's performance. Meanwhile, total assets turnover, inventory turnover and debt to equity ratio have shown insignificantly affecting the firm's performance.